Vitamin B12, Folic acid and Homocysteine Levels in female metabolic syndrome patients and their relationship with Heart rate variability. - Akter, Khaleda; Akter, Halima; Nurjahan, Fatema; Sultana, Shamima; Begum, Shelina (Journal of Bangladesh Society of Physiologist, 2021)
Background: Metabolic syndrome (MeS) is a well-recognized risk factor for cardiovascular diseases. It is associated with hyperhomocysteinemia resulting from deficiency of vitamin B12 and folic acid. Both the MeS and hyperhomocysteinemia adversely affect heart rate variability. Objectives: To assess vitamin B12, folic acid and homocysteine levels in female metabolic syndrome patients and their relationship with heart rate variability. Methods: After taking ethical clearance from Institutional Review Board (IRB) of Bangabandhu Sheikh Mujib Medical University (BSMMU) this cross sectional study was conducted on 80 female subjects of 25-45 years of age. Among them 40 metabolic syndrome patients were included in the study group and 40 age matched apparently healthy female constituted control group. All the patients were enrolled from Outpatient Department of Endocrinology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh according to selection criteria. Serum vitamin B12, folic acid, homocysteine level was estimated by chemiluminescent immunoassay and frequency domain parameters of Heart Rate Variability (HRV) was recorded by a data acquisition device, Powerlab 8/35, AD instruments, Australia. Statistical aalysis was done by independent sample ‘t’ test and pearson correlation test. Results: In this study, among frequency domain HRV variables Total power(TP), low frequency power(LF), high frequency power (HF), HF normalized unit(nu) were significantly lower (p<0.05) and LF nu, LF/HF were significantly higher (p<0.05) in MS patients compared to those of control. In addition, no significant changes (p>0.05) were found in serum vitamin B12, folic acid and homocysteine levels between these two groups. But on correlation analysis only the folic acid level was significantly negatively correlated (p<0.05) with LF and HF power. Conclusion: The present study revealed that the folic acid level but not the vitamin B12 and homocysteine levels has significant negative correlation with heart rate variability in female MS. J Bngladesh Soc Physiol 2021;16(1): 24-32